Factors Associated with Physical Inactivity among Adult Urban Population of Puducherry, India: A Population Based Cross-sectional Study - Ariarathinam Newtonraj; Natesan Murugan; Zile Singh; Ramesh Chand Chauhan; Anandan Velavan; Manikandan Mani (Journal of Clinical and Diagnostic Research, 2017)
Introduction: Physical inactivity is the fourth leading cause of death worldwide. Increase in physical activity decreases the incidence of cardiovascular diseases, Type 2 diabetes, stroke, and improves psychological wellbeing. Aim: To study the level of physical inactivity among the adult population in an urban area of Puducherry in India and its associated risk factors. Materials and Methods: This cross-sectional study was conducted among 569 adult participants from an urban area of Pondicherry. The level of physical inactivity was measured by using WHO standard Global Physical Activity Questionnaire (GPAQ). Results: Overall prevalence of physical inactivity in our study was 49.7% (CI: 45.6-53.8). Among the physically active people, contribution of physical activity by work was 77.4%, leisure time activities were 11.6% and transport time was 11%. Both men and women were equally inactive {Physically inactive among women was 50% (CI:44.1-55.9)} and {Physically inactive among men was 49.5% (CI:43.8-55.2)}. Prevalence of physical inactivity was increasing with increasing age. Non tobacco users were two times more active than tobacco users {Adjusted Odds Ratio: 2.183 (1.175- 4.057)}. Employed were more active as compared to retired {Adjusted Odds Ratio: 0.412 (0.171- 0.991)}, students {Adjusted Odds Ratio: 0.456 (0.196-1.060)}, house wives {Adjusted Odds Ratio: 0.757 (0.509-1.127)} and unemployed {Adjusted Odds Ratio: 0.538 (0.271-1.068)}. Non alcoholics were only 0.34 times as active as alcoholics. Conclusion: Level of physical activity was found to be insufficient among adult urban population of Puducherry. Working adult population found to be active, that too due to their work pattern. There is a need to promote leisure time and travelling time physical activity.